Democratic decoupling. Issue 1 (2nd January 2021) - Ding, Iza; Slater, Dan
ABSTRACT: Democratic backsliding does not necessarily see all democratic institutions erode in parallel fashion. This article analyses contemporary democratic backsliding through the lens of institutional change, as a process of "democratic decoupling, " in which a systematic gap opens up between the constitutive features of liberal democracy. Specifically, we focus on the worldwide decoupling between electoral quality and rights protections over the past decade. Using global data from the V-Dem project, we establish that elections are improving and rights are retracting in the same time period, and in many of the same cases. We offer several illustrative examples from Asia of illiberal juggernauts who have ridden the waves of free and fair elections to do great damage to rights protections, focusing primarily on Narendra Modi and the ruling BJP in the world's largest democracy, India.